Use of Twitter, online forum and blog for collaborative learning among ESL undergraduates learners - Arshad, Aqilah (2018)
Social Media sites can be used by learners, as a platform for information gathering and interaction during collaborative learning activities. However, there is little research on the tertiary learners’ experiences and language analysis in the use of social media for collaborative learning. Positive experiences while using social media applications may contribute to better learning outcomes. Thus, this study aims to investigate ESL learners’ perception, experiences, preference and functional moves of Twitter, Online Forum and Blog for collaborative learning.The study employs quantitative and qualitative data collection methods involving seventy-seven ESL learners from an intact class enrolled for an English course at a public university in Malaysia. The learners had to complete nine learning tasks designed for the different social media platforms. An online questionnaire survey was used to gather quantitative data. It referred to the Technology Acceptance Model (TAM) regarding its perceived usefulness and perceived ease of use. Meanwhile, focused groups interviews were conducted to examine the learners’ positive and negative aspects of their collaborative learning experience and their preferred social media platforms. The Computer-Mediated Discourse Analysis (CMDA) approach was used in analyzing the functional moves on the three social media platforms. Overall, the results of the learners’ perceived usefulness and ease of use were different for each social media. Twitter was considered the preferred social media platform by learners in completing the learning tasks. The learners perceived Twitter as a highly interactive social media platform that helped them in their learning and social purposes. The analysis of functional moves revealed that there is evidence of the learners interacting collaboratively in accomplishing the task. More insights and information for the implementation of collaborative learning while using the social media can promote active learning that fits the current generation in live with demand for the Industrial Revolution 4.0.